Chronic Heart Failure: We Are Fighting the Battle, but Are We Winning the War? - John J. Atherton (Scientifica)
Heart failure represents an end-stage phenotype of a number of cardiovascular diseases and is generally associated with a poor prognosis. A number of organized battles fought over the last two to three decades have resulted in considerable advances in treatment including the use of drugs that interfere with neurohormonal activation and device-based therapies such as implantable cardioverter defibrillators and cardiac resynchronization therapy. Despite this, the prevalence of heart failure continues to rise related to both the aging population and better survival in patients with cardiovascular disease. Registries have identified treatment gaps and variation in the application of evidenced-based practice, including the use of echocardiography and prescribing of disease-modifying drugs. Quality initiatives often coupled with multidisciplinary, heart failure disease management promote self-care and minimize variation in the application of evidenced-based practice leading to better long-term clinical outcomes. However, to address the rising prevalence of heart failure and win the war, we must also turn our attention to disease prevention. A combined approach is required that includes public health measures applied at a population level and screening strategies to identify individuals at high risk of developing heart failure in the future.